Measuring and monitoring change in a strategic business context: Considerations on the role of organizations' composition elements - Tudor Irimiaș (CES Working Papers, 2021)
This paper brings theoretical arguments that support good business administration practices. The European business environment (see the EU motto: united in diversity) is as homogeneous in terms of legislative areas (i.e., the single market, economic and monetary union, fair competition practices), as heterogeneous in terms of particularities and cultural, regional and local contexts, which can be methodically extracted through the PEST analysis (political, economic, social and technological). In this business context but also of the desideratum of any organization to generate added value, regardless of its nature, the process of quantifying the status quo of the organization must be considered as a decisive factor in the change management process. The organization's strategy has to be therefore translated into criteria that are compatible with its goals and quantifiable - only then will it be possible to adequately assess the results of implementation. In the following lines I present the methodological norms for quantifying the status quo of an organization, as well as the potential types of indicators needed.
Keywords: 330; strategic management; organisational change; change indicators; strategicstatus quo